Individual variation in biomarkers of health: influence of persistent organic pollutants in Great Skuas (Stercorarius Skua) breeding at different geographical locations - Bourgeon, S.; Leat, E.H.K.; Magnusdóttir, E.; Fisk, A.T.; Furness, R.W.; Strøm, H.; Hanssen, S.A.; Petersen, Æ.; Olafsdóttir, K.; Borgå, K.; Gabrielsen, G.W.; Bustnes, J.O. (Environmental Research, 2012)
Persistent organic pollutants (POPs) have been shown to cause adverse effects on a number of biomarkers of health in birds. POPs may impair immune function and alter the stress response, defined as a suite of behavioral and physiological responses to environmental perturbations. Recent studies have also proposed that POPs can induce oxidative stress. Nevertheless, there is a lack of studies simultaneously assessing the potential damaging effects of POPs on the latter biomarkers. In this study, we examined the contribution of legacy (organochlorines; (OCs)) and emerging (flame retardants; PBDEs) POPs to individual variations in stress levels (feather corticosterone), humoral immunity (plasma immunoglobulin Y levels) and oxidative stress occurring in three breeding colonies of a top predator seabird, the Great skua (Stercorarius skua), distributed from temperate regions to the high Arctic: Shetland (60°N), Iceland (63°N) and Bjørnøya (74°N). Our results demonstrated that plasma concentrations of OCs in Great skuas from Bjørnøya are among the highest in North Atlantic seabirds, with up to 7900 μg/kg (ww) ∑OCs. Yet, a latitudinal gradient in POP levels was observed with all compounds being significantly higher in Bjørnøya than in Iceland and Shetland (on average 4-7 fold higher for OCs and 2.5-4.5 for PBDEs, respectively). Contrary to our predictions, skuas breeding at the least contaminated site (i.e., Shetland) experienced the poorest physiological condition; i.e., the highest levels of stress hormones (25% higher) and oxidative stress (50% higher) and the lowest immunoglobulin levels (15% lower) compared to the two other colonies. Finally, our results failed to point out consistent within-colony relationships between biomarkers of health and POPs. Overall, it is suggested that other ecological factors such as food availability could constrain physiological indicators more than anthropogenic contaminants.